TelNet - a database for human and yeast genes involved in telomere maintenance - Delia M. Braun; Inn Chung; Nick Kepper; Katharina I. Deeg; Karsten Rippe (BMC Genetics, 2018)
Abstract Background The ends of linear chromosomes, the telomeres, comprise repetitive DNA sequences in complex with proteins that protects them from being processed by the DNA repair machinery. Cancer cells need to counteract the shortening of telomere repeats during replication for their unlimited proliferation by reactivating the reverse transcriptase telomerase or by using the alternative lengthening of telomeres (ALT) pathway. The different telomere maintenance (TM) mechanisms appear to involve hundreds of proteins but their telomere repeat length related activities are only partly understood. Currently, a database that integrates information on TM relevant genes is missing. Description To provide a resource for studies that dissect TM features, we here introduce the TelNet database at http://www.cancertelsys.org/telnet/. It offers a comprehensive compilation of more than 2000 human and 1100 yeast genes linked to telomere maintenance. These genes were annotated in terms of TM mechanism, associated specific functions and orthologous genes, a TM significance score and information from peer-reviewed literature. This TM information can be retrieved via different search and view modes and evaluated for a set of genes as demonstrated for an exemplary application. Conclusion TelNet supports the annotation of genes identified from bioinformatics analysis pipelines to reveal possible connections with TM networks. We anticipate that TelNet will be a helpful resource for researchers that study telomeres.